2005
DOI: 10.1177/0007650305275305
|View full text |Cite
|
Sign up to set email alerts
|

Business-Government Relations Within a Contingency Theory Framework: Strategy, Structure, Fit, and Performance

Abstract: Using a contingency theory framework, this study examines the relationship between a firm’s business-government relations (BGR) strategy, BGR structure, and BGR performance. Based on previous work, the study hypothesizes that BGR strategy determines, in part, the structure of the public affairs function, as well as the function’s effectiveness. Furthermore, the study contends that an appropriate fit between BGR strategy and BGR structure leads to improved BGR performance. Results indicate that there is a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…The contingency theory approach is explained as an approach for organizations with system adjustments to achieve agency goals so that their performance is achieved as seen from the organizational environment. This theory explains that organizational performance depends on various factors in particular, organizations must consider their internal capabilities as well as external conditions in planning steps (strategies) to succeed in achieving organizational goals (Meznar & Johnson, 2005). In this regard, the achievement of organizational goals is associated with accountability or a form of accountability for its role as a public sector organization.…”
Section: Contingency Theorymentioning
confidence: 99%
“…The contingency theory approach is explained as an approach for organizations with system adjustments to achieve agency goals so that their performance is achieved as seen from the organizational environment. This theory explains that organizational performance depends on various factors in particular, organizations must consider their internal capabilities as well as external conditions in planning steps (strategies) to succeed in achieving organizational goals (Meznar & Johnson, 2005). In this regard, the achievement of organizational goals is associated with accountability or a form of accountability for its role as a public sector organization.…”
Section: Contingency Theorymentioning
confidence: 99%
“…Hasil tersebut menegaskan bahwa pengaruh GUG terhadap kinerja dapat dilihat dari kinerja PT. Hasil tersebut mementahkan temuan (Meznar & Johnson Jr, 2005), yang justru menunjukkan tidak ada hubungan yang jelas antara struktur governance dengan kinerja. Dengan demikan dapat dikatakan semakin baik GUG maka Kinerja Perguruan Tinggi semakin baik pula.…”
Section: Pembahasanunclassified
“…The importance of PA adaptation to changes in the firm's operating environment has been further emphasized by Meznar and Johnson (2005). They found that PA performance was a function of how well a firm's PA strategy "fit" with other characteristics of the firm.…”
Section: Public Affairs Adaptation To Environmental and Operating Condition Changesmentioning
confidence: 99%